Risk Factors for Delirium in the Palliative Care Population: A Systematic Review and Meta-Analysis - Guo, Duan; Lin, Taiping; Deng, Chuanyao; Zheng, Yuxia; Gao, Langli; Yue, Jirong (Frontiers in Psychiatry, 2021)
Objective: Delirium is common and highly distressing for the palliative care population. Until now, no study has systematically reviewed the risk factors of delirium in the palliative care population. Therefore, we performed a systematic review and meta-analysis to evaluate delirium risk factors among individuals receiving palliative care. Methods: We systematically searched PubMed, Medline, Embase, and Cochrane database to identify relevant observational studies from database inception to June 2021. The methodological quality of the eligible studies was assessed by the Newcastle Ottawa Scale. We estimated the pooled adjusted odds ratio (aOR) for individual risk factors using the inverse variance method. Results: Nine studies were included in the review (five prospective cohort studies, three retrospective case-control studies and one retrospective cross-section study). In pooled analyses, older age (aOR: 1.02, 95% CI: 1.01-1.04, I² = 37%), male sex (aOR:1.80, 95% CI: 1.37-2.36, I² = 7%), hypoxia (aOR: 0.87, 95% CI: 0.77-0.99, I² = 0%), dehydration (aOR: 3.22, 95%CI: 1.75-5.94, I² = 18%), cachexia (aOR:3.40, 95% CI: 1.69-6.85, I² = 0%), opioid use (aOR: 2.49, 95%CI: 1.39-4.44, I² = 0%), anticholinergic burden (aOR: 1.18, 95% CI: 1.07-1.30, I² = 9%) and Eastern Cooperative Oncology Group Performance Status (aOR: 2.54, 95% CI: 1.56-4.14, I² = 21%) were statistically significantly associated with delirium. Conclusion: The risk factors identified in our review can help to highlight the palliative care population at high risk of delirium. Appropriate strategies should be implemented to prevent delirium and improve the quality of palliative care services.